2019
DOI: 10.2464/jilm.69.548
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state bonding of A6061/high-tensile steel plate by metal salt generation bonding technique with acetic acid

Abstract: The effect of aluminum acetate coating treatment on the bod strength of the solid-state bonded interface of A6061 aluminum alloy and high-tensile steel plate was investigated by SEM observation of fractured surfaces and interfacial microstructures. The surface of the aluminum alloy was coated by boiling in 5% aqueous solution of NaOH for 20 s and 99.7% acetic acid. Bonding process was performed at bonding temperature of 713-753 K under a load of 20 MPa and bonding time of 900 s. As the result of this study, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…15) Furthermore, it was found that the bonding strength of A6061 aluminum alloy and high-strength steel sheet was greatly improved by applying an acetate film to the aluminum alloy side before solid phase bonding. 16) In recent years, nonelectrolyte NiP plating has come to be used on the copper wiring of print-wiring boards to control the formation of a brittle intermetallic compound layer at the interface between the solder and copper wiring. Nonelectrolyte NiP plating has attracted attention as an UBM (Under Bump Metallization) process because the rate of reaction with solder is slow, and numerous studies have been conducted on the bond interface and its mechanical properties in response to the operating environment (e.g., high temperature).…”
Section: Introductionmentioning
confidence: 99%
“…15) Furthermore, it was found that the bonding strength of A6061 aluminum alloy and high-strength steel sheet was greatly improved by applying an acetate film to the aluminum alloy side before solid phase bonding. 16) In recent years, nonelectrolyte NiP plating has come to be used on the copper wiring of print-wiring boards to control the formation of a brittle intermetallic compound layer at the interface between the solder and copper wiring. Nonelectrolyte NiP plating has attracted attention as an UBM (Under Bump Metallization) process because the rate of reaction with solder is slow, and numerous studies have been conducted on the bond interface and its mechanical properties in response to the operating environment (e.g., high temperature).…”
Section: Introductionmentioning
confidence: 99%